The Role of Green Industry in Achieving the Dimensions of Sustainable Development. (Al-Farooq Journal of Sciences, 2026)
This study aimed to examine the role of green industry in achieving the economic, social, and environmental dimensions of sustainable development through reviewing and analyzing relevant literature and previous studies related to green industry and sustainability. The study adopted the descriptive-analytical approach by reviewing recent scientific studies and international reports associated with the research topic.The findings revealed that green industry represents a strategic approach to achieving sustainable development through reducing pollution and carbon emissions, improving energy and resource efficiency, enhancing economic competitiveness, and contributing to job creation and environmental improvement. The study also identified several challenges facing the implementation of green industry, particularly in developing countries, including weak industrial infrastructure, high costs of clean technologies, and limited environmental policies.The study recommended the adoption of national policies and strategies supporting green industry, increasing investment in clean technologies, promoting scientific research and innovation, and strengthening environmental legislation to support sustainable development goals.
Keywords: Green Industry, Sustainable Development, Green Economy, Clean Technologies, Industrial Sustainability, Environmental Pollution.